Intestinal failure after bariatric surgery: Treatment and outcome at a single-intestinal rehabilitation and transplant center - Wethit Dumronggittigule (2020)
© 2018 American Society for Bariatric Surgery Background: Though intestinal failure (IF) after bariatric surgery (BS) is uncommon, its prevalence is increasing. However, data on the outcomes for these patients are limited. Objectives: To analyze the outcomes of treatment for patients with IF after BS. Setting: University hospital. Methods: A single-center analysis (1991–2016) of outcomes according to treatment arms established by a multidisciplinary team. Results: Twenty-five IF patients were identified (median age 45 yr). BS was 92% Roux-en-Y gastric bypass. The major cause of IF was volvulus/internal hernia (72%). Median time from BS to IF was 48 months. Treatment arms were intestinal rehabilitation (IR, n = 15), transplantation (TXP, n = 5), and parenteral nutrition (PN, n = 5). For IR, median bowel length was 60 cm. Forty-six percent ultimately discontinued PN. Twenty-seven percent were partially weaned PN and 27% failed IR. Common surgical rehabilitation was Roux-en-Y gastric bypass reversal and restoration of gastrointestinal continuity. The 5-year overall survival was 74%. For TXP, 7 patients were listed for TXP (5 initially and 2 after failed IR). Three underwent TXP, 2 isolated intestine and 1 isolated liver. Three were delisted (1 improvement and 2 death). For PN, 6 patients required long-term PN (5 initially and 1 after failed IR). Four patients are alive currently. Conclusions: IF after BS is an increasing problem facing IR centers. Internal hernia is the major cause. Surgical IR is the first-line therapy and affords the best outcome. TXP is reserved for rescuing patients who failed IR or develop PN complications. Long-term PN is suitable for patients in whom IR or TXP is impractical.